Sex Differences in Parent and Child Pain Ratings during an Experimental Child Pain Task - Erin C Moon; Christine T Chambers; Anne-Claire Larochette; Kelly Hayton; Kenneth D Craig; Patrick J McGrath (Pain Research and Management)
Research in the field of pediatric pain has largely ignored the role of fathers in their children’s pain experiences. The first objective of the present study was to examine the effect of the presence of mothers versus fathers on children’s subjective ratings, facial expressions and physiological responses to acute pain. The second objective was to examine whether child and parent sex influence parents’ proxy ratings of their children’s pain. The final objective was to compare levels of agreement between mothers’ and fathers’ assessments of their children’s pain. Participants included 73 children (37 boys, 36 girls), four to 12 years of age, along with 32 fathers and 41 mothers. Children undertook the cold pressor pain task while observed by one of their parents. During the task, the children’s heart rates and facial expressions were recorded. Children provided self-reports and parents provided proxy reports of child pain intensity using the seven-point Faces Pain Scale. Neither child nor parent sex had a significant impact on children’s subjective reports, facial expressions or heart rates in response to acute pain. Fathers gave their sons higher pain ratings than their daughters, whereas mothers’ ratings of their sons’ and daughters’ pain did not differ. Kappa statistics and t tests revealed that fathers tended to be more accurate judges of their children’s pain than mothers. Overall, this research highlights the importance of examining both parent and child sex differences in pediatric pain research.